2011
DOI: 10.4067/s1726-569x2011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Ethical health technology assessment in Latin America: lessons from Canada and Argentina

Abstract: A wide array of biomedical and genetic technologies is becoming available in both developed and developing nations. This situation is the cause of growing concern for health policy makers who must evaluate the utility of these technologies for their inclusion in public health insurance programs. Ideally, policy makers would have the information necessary to rationally allocate scarce resources, prioritise technologies, and ensure fair access to necessary health care services. The reality, however, is that poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
4
0
4
Order By: Relevance
“…Table 3 shows the survey section's results on HTA process and report, whereby participants were asked whether they agree with various proposed aims for HTA according to three following statements: (i) they should concentrate on one phase: assessment , which includes epidemiological studies, the collection of all available scientific information (e.g., literature review and cost-effectiveness analyses) and then a subsequent analysis and final synthesis; (ii) “Following Blanquaert & Caron the process of HTA can be described as a combination of two phases”: (a) assessment (as described above); and (b) appraisal , in which contextualized data are gathered and recommendations made (20); and (iii) three phases: (a) assessment (as described above); (b) contextual data , including ethical analyses and qualitative studies on patients and citizens perspective, organizational changes and so on, and a subsequent analysis and synthesis; and (c) recommendations grounded in the first two phases.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the survey section's results on HTA process and report, whereby participants were asked whether they agree with various proposed aims for HTA according to three following statements: (i) they should concentrate on one phase: assessment , which includes epidemiological studies, the collection of all available scientific information (e.g., literature review and cost-effectiveness analyses) and then a subsequent analysis and final synthesis; (ii) “Following Blanquaert & Caron the process of HTA can be described as a combination of two phases”: (a) assessment (as described above); and (b) appraisal , in which contextualized data are gathered and recommendations made (20); and (iii) three phases: (a) assessment (as described above); (b) contextual data , including ethical analyses and qualitative studies on patients and citizens perspective, organizational changes and so on, and a subsequent analysis and synthesis; and (c) recommendations grounded in the first two phases.…”
Section: Resultsmentioning
confidence: 99%
“…The argument structure of the report involves decision concerning five steps (see Table 1 Steps 11 to 15). The distinction between assessment and appraisal proposes a way of reporting the research findings as reported by Martin and colleagues: "Following Blanquaert & Caron the process of HTA can be described as a combination of two phases: 1) assessment, which includes epidemiological studies, the collection of all available scientific information (e.g., literature review, cost-effectiveness analyses) and then a subsequent analysis and synthesis; and 2) appraisal, in which contextualised studies are conducted and recommendations made" (Martin et al, 2011). In this scheme, the report's structure is based on a distinction between "scientific information" and "contextualized studies".…”
Section: Choice Of External Reviewersmentioning
confidence: 99%
“…However, in this scheme, it is not clear how the results of contextualized studies should be presented. Finally, since recommendations are a part of the appraisal phase, the assessment phase's results should be integrated with those of contextual studies in the recommendations according to this scheme (Martin et al, 2011).…”
Section: Choice Of External Reviewersmentioning
confidence: 99%
“…El manejo sensacionalista de los medios produce un desajuste en relación con las medidas que podrían tomarse para mejoras en salud y desarrollo social, de acuerdo con bases científicas y participación ciudadana (27). Contar con la información adecuada, posibilitaría que los responsables de formular políticas pudieran asignar, de una manera racional, los escasos recursos disponibles en países en desarrollo, priorizando tecnologías y asegurando acceso equitativo, pero esto a menudo no ocurre (28).…”
Section: Definir Los Límites Entre Artificial Y Naturalunclassified